ANALISIS PENGARUH KUALITAS LAYANAN, LOKASI, DAN E-PAYMENT TERHADAP KEPUASAN PELANGGAN (Studi Pada Pelanggan fitness center Elise Ladies Gym Semarang) - Grace Aryunitami Gultom; Yoestini Yoestini (Diponegoro Journal of Management, 2022)
The development of the fitness center in the city of Semarang is growing rapidly. However, it is very rare to find a fitness center specifically for women in Semarang, especially in the Tembalang area, Central Java. One of the fitness centers that is aware of the importance of health sports for women and can provide a sense of security in carrying out sports activities, one of which is the Elise Ladies Gym. Elise Ladies Gym is a fitness center for women only. Unfortunately, based on data from Elise Ladies Gym visitor reports from 2019-March 2022, there was a 50% decrease in customers from 2020-2021. Based on the pre-observation with the interview method conducted by the author on the Elise Ladies Gym fitness center customers, it shows that Service Quality, Location and E-payment are one of the factors. On this basis, the authors are interested in further research regarding the effect of Service Quality, Location and E-payment on Customer Satisfaction at the Elise Ladies Gym fitness center Semarang. This research was conducted with a qualitative approach with a questionnaire or questionnaire as primary data. The total sample used in this study amounted to 62 respondents. The data obtained were then analyzed by multiple linear regression with the help of Software Statistical Product and Service Solution (SPSS) version 20. As a result, Service Quality, Location and E-payment had a positive effect on customer satisfaction at Elise Ladies Gym.